Pembangunan Berkelanjutan Berdasarkan Konsep Tri Hita Karana untuk Kegiatan Ekowisata - I Wayan Runa (Pusat Kajian Bali Universitas Udayana, 2012)
AbstractBalinese society has from a long time ago managedand developed their land based on environmentallyfriendly principles. These principles have been inspired byimplementations of the Balinese Tri Hita Karana conception. Thisarticle attempts to explain various spatial developments relatingto ecotourism activities that are founded by Tri Hita Karanavalues and practices. It constructs its arguments by conductingan intensive literature study to review relevant hypotheses andconcepts proposed by scholars in the field. The article concludesthat ecotourism is a form of environmentally friendly touristdevelopments and is seen to be the most sustainable modelfor future’s tourism. The article completes its conclusion byunderlining that for its success, ecotourism related developmentpractices should be first understood. It then should come witha certain framework and standard for its implementations. Bestpractices pertaining to the ecotourism development should becertified and accessible by public and others parties involved. Inaddition to these remarks, the article conclusively proposes TriHita Kharana conception as a framework that offers guidancefor sustainably developed ecotourism. This local concept alsoprovides direction as to how its development and its impact onspatial development can be approached and managed, especiallyto the case of Bali.